2008
DOI: 10.1111/j.1447-0756.2008.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternity waiting homes in Southern Lao PDR: The unique ‘silk home’

Abstract: The concept of maternity waiting homes (MWH) has a long history spanning over 100 years. The research reported here was conducted in the Thateng District of Sekong Province in southern Lao People's Democratic Republic (PDR) to establish whether the MWH concept would be affordable, accessible, and most importantly acceptable, as a strategy to improve maternal outcomes in the remote communities of Thateng with a high proportion of the population from ethnic minority groups. The research suggested that there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 4 publications
(8 reference statements)
10
55
0
Order By: Relevance
“…These findings are similar to many developing countries, including Laos (Eckermann and Deodato, 2008), Pakistan (Shaikh and Hatcher, 2005), Nigeria (Onah et al, 2006), Uganda (Amooti- Kaguna and Nuwaha, 2000), Tanzania (Magoma et al, 2010), Burkina Faso (Some et al, 2011) and Indonesia (Titaley et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…These findings are similar to many developing countries, including Laos (Eckermann and Deodato, 2008), Pakistan (Shaikh and Hatcher, 2005), Nigeria (Onah et al, 2006), Uganda (Amooti- Kaguna and Nuwaha, 2000), Tanzania (Magoma et al, 2010), Burkina Faso (Some et al, 2011) and Indonesia (Titaley et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…A number of studies reported that simply building a MWH did not overcome barriers to accessing care as women still needed financial resources to get to the MWH [15, 17, 25, 28, 30]. The cost of public transportation to reach the MWH was a common barrier to its use and varied depending on the mode of transport distance and time of day [13].…”
Section: Resultsmentioning
confidence: 99%
“…One of the tested and proven strategies is the establishment of maternity waiting homes a practice which has been in existence for more than 100 years [9][10][11] . In developing countries even under the best of times, the delivery rate in health facilities is less than 30% with as low as 15% in other settings 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the unscheduled nature of deliveries and the preponderance for deliveries to occur at night compounded by nonavailability of transport and ambulance services, the need for maternity waiting homes becomes apparent 9 . Pregnancy outcomes from high risk pregnancies for mothers who delivered in maternity waiting homes were reported to be similar or better than those who delivered in the home under the services of TBAs 2 .…”
Section: Discussionmentioning
confidence: 99%